2019
DOI: 10.1128/aem.00258-19
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Active Ammonia Oxidizers and Nitrification Activity in Eutrophic Lake Sediments to Nitrogen and Temperature

Abstract: Ammonium concentrations and temperature drive the activities of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB), but their effects on these microbes in eutrophic freshwater sediments are unclear. In this study, surface sediments collected from areas of Taihu Lake (China) with different degrees of eutrophication were incubated under three levels of nitrogen input and temperature, and the autotrophic growth of ammonia oxidizers was assessed using 13C-labeled DNA-based stable-isotope probing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Contrary to findings of most studies on low-elevation rivers (16), average AOB amoA gene abundance was significantly higher than that of AOA in this study. In the slightly eutrophic and cold lake sediments (10°C), AOB amoA gene abundance has also been found to be greater than that of AOA (30).…”
Section: Discussionmentioning
confidence: 95%
“…Contrary to findings of most studies on low-elevation rivers (16), average AOB amoA gene abundance was significantly higher than that of AOA in this study. In the slightly eutrophic and cold lake sediments (10°C), AOB amoA gene abundance has also been found to be greater than that of AOA (30).…”
Section: Discussionmentioning
confidence: 95%
“…The ammonia compound content in the groundwater sample was relatively high compared to the ammonia content in natural waterways (less than 0.1 mg/L). This indicates organic pollution from domestic waste because, when a closer look is taken, the groundwater sampling location was in the vicinity of a human settlement that produced organic wastes like domestic one [23].…”
Section: A Preliminary Testmentioning
confidence: 99%
“…The results of the analysis of the nutritional contents of the groundwater [18], including carbon (C), nitrogen (N), phosphor (P), and potassium (K) (Table 2). Plants highly demand major nutrients like C, N, P, and K. The groundwater availability in the groundwater indicates that aquatic plants will grow well and support the phytoremediation process [23].…”
Section: A Preliminary Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen, Ouyang, Zhu, and Trimmer (2019b) found that anaerobic ammonium oxidation (anammox) and nitrite-dependent anaerobic methane oxidation (n-damo) in permeable riverbed sediments were spatially separated, potentially removing any competition for nitrite. Nitrogen input and temperature change impacted the activities of ammonia-oxidizing archaea and bacteria in eutrophic sediments from Taihu Lake, China (Wu, Han, Zhu, & Zhong, 2019).…”
Section: Annual Literature Reviewmentioning
confidence: 99%